Randomized Control Trial of Kangaroo Mother Care in Low Birth Weight Babies at a Tertiary Level Hospital - Acharya, N; Singh, RR; Bhatta, NK; Poudel, P (Journal of Nepal Paediatric Society, 2014)
Introduction: This study was conducted to compare the effect of Kangaroo Mother Care (KMC) and conventional methods of care on weight gain, occurrence of hypothermia and apnea and duration of hospital stay among Low Birth Weight (LBW) babies. Materials and Methods: It was a randomized control trial conducted at a tertiary level hospital for a period of one year from June 2009 to May 2010. Total 126 stable LBW babies weighing less than 2000 gm and fulfilling inclusion criteria were included in the study. Neonates enrolled for the study were allocated to either KMC or control group using random number table. KMC group was subjected to Kangaroo mother care of at least six hours per day in not more than four sittings. In control group, babies were adequately clothed, covered and kept with their mother and if required were kept under radiant warmer. Recording of temperature in KMC group was done before, during and after KMC. In control group temperature was taken every 4 hours. Weighing of baby was done twice daily on electronic weighing scale. Results: Median daily weight gain (IQR) was 10 (6- 20) gm in KMC group as compared to 7 (0-10) gm in control group (p<0.001). Mean weight gain was 12.11±9.04 gm in KMC group as compared to 3.29±15.81 gm in control group (p<0.001). Incidence of hypothermia was more in control group (12.6%) as compared to KMC group (3.1%) (p=0.048). Duration of hospital stay was less in control group as compared to KMC group (p=0.015). Conclusion: LBW babies less than 2000 gm who receive KMC show better weight gain and have less incidence of hypothermia than those who do not receive KMC. DOI: http://dx.doi.org/10.3126/jnps.v34i1.8960 J Nepal Paediatr Soc 2014;34(1):18-23